Economía colaborativa, colonialidad de datos y mujeres racializadas - González Ortuño, Gabriela (Comparative Cultural Studies - European and Latin American Perspectives, 2022)
This article seeks to demonstrate the way in which he deployment of mediation technologies in the collaborative economy (apps) sustains and deepens the labor exploitation of racialized women. These mediations developed by companies, mostly from the global North, promote data extractivism and are positioned as North-South exploitation tools in the same sense as other forms that can be recognized as part of coloniality structures such as precariousness. labor, the increase in working hours and the cancellation of free time and circulation of the gift that especially affects women.